Larvicidal efficacy of green synthesized silver nanoparticles using Coleus aromaticus and Wrightia tinctoria against Aedes aegypti - Kaliyamoorthy Dass; Nagamuthu Prakash; Pitchaimuthu Mariappan (Next Materials)
Mosquitoes transmit a number of serious diseases, including brain fever, chikungunya, dengue fever, filariasis, hemorrhagic fever, Japanese encephalitis, malaria, dengue, and Zika. Whereas the synthetic chemical insecticides are commonly used for mosquito control, and it caused physiological resistance to mosquito species and significant effects on humans and the environment. As a result, plant-based insecticides have emerged as an attractive one. Recent research has revealed that green-synthesized silver nanoparticles derived from plant extracts have significant larvicidal properties. In the scenario we focused on application of nanotechnology. Nanotechnology is an emerging field of science and technology, it has incredible potential in pest management, medicine, and other fields. In this regards current investigation focused on the larvicidal and pupicidal effect of green-synthesized silver nanoparticles using C. aromaticus and W. tinctoria on second, third, and fourth-instar and pupa of Aedes aegypti. The green synthesized silver nanoparticles characterized by UV-Vis spectroscopy, FTIR, XRD, and SEM. The 24-hour LC50 and LC90 values obtained from C. aromatics and W. tinctoria synthesized silver nanoparticles against Ae. aegypti second, third, and fourth instars and pupae. The results showed that green synthesized silver nanoparticles from C. aromaticus are more effective than W. tinctoria nanoparticles used.